IMPROVING MIDWIVE’S CAPACITY TO PROVIDE PREGNANCY AND EARLY POSTPARTUM EXERCISE - Sri Artina Dewi, Ni Nyoman; Panselina Widowati, Lorensia; Suci Dwi Aningsih, Baharika; Suhaid, Dewi Novitasari; Margaretha Manungkalit, Eviyani; Kartiko Kusumo Wardani, Dyah Woro; Leoni Irawan, Yetty; Ida, Agustina (LPPM Univ. Ibn Khaldun Bogor, 2023)
Low back pain is frequently reported by pregnant women. It is caused by the shifts of center of balance as the mother's weight increases and uterus expands. The inability to adjust to these changes, muscle and ligament weakness can make it more prone to pain. Midwives as a frontliner in maternal health, is supposed to be able to apply health promotion to encourage exercise for expectant mothers and new mothers in the early postpartum period. One of them is by giving women and new mothers pregnancy and early postpartum exercise. The purpose of this act of community service was to enable midwives to accompany more women during pregnancy and the first few weeks after giving birth. The method proposed is to provide information on ethics, planning, direction, and evaluation of pregnancy and early postpartum exercise, provide information on anti-corruption, and manage the process of operating this training activity from beginning to end. There were 24 participants in the course, all of them currently employed as midwives for the Siloam Hospital Group. The course was considered successful after receiving an improving score of all participants.